International Monetary Fund Annual Report 1975. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1975)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1975. The report highlights that by traditional standards, the performance of the world economy during 1974 and the first half of 1975 was poor. But by reference to the serious and complex range of problems that had to be confronted, this performance can be characterized as mixed. The slowdown of economic growth in the industrial world that was in process around the beginning of 1974 developed into an unexpectedly severe and widespread recession featuring exceptionally high rates of unemployment.